2016
DOI: 10.1039/c6ta05958a
|View full text |Cite|
|
Sign up to set email alerts
|

β-Cyclodextrin modified graphitic carbon nitride for the removal of pollutants from aqueous solution: experimental and theoretical calculation study

Abstract: The enhanced interaction of β-cyclodextrin modified graphitic carbon nitride (g-C3N4/β-CD) or g-C3N4 with methyl orange (MO) or Pb(ii) in natural environmental remediation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
69
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(72 citation statements)
references
References 66 publications
3
69
0
Order By: Relevance
“…It is noteworthy that the amine band of β‐CD/g‐C 3 N 4 shows an obvious blue shift compared with that of the pristine g‐C 3 N 4 which may be ascribed to the hydrogen bond formed between O‐H of β‐CD and N‐H of g‐C 3 N 4 . This result is consistent with Zou's study …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It is noteworthy that the amine band of β‐CD/g‐C 3 N 4 shows an obvious blue shift compared with that of the pristine g‐C 3 N 4 which may be ascribed to the hydrogen bond formed between O‐H of β‐CD and N‐H of g‐C 3 N 4 . This result is consistent with Zou's study …”
Section: Resultssupporting
confidence: 93%
“…Graphite carbon nitride (g-C 3 N 4 ), a new type of inorganic free-metallic fluorescent material, has been widely investigated in bioimaging 5,6 and biosensing 7-10 due to its unique features of good biocompatibility, low cost, simple preparation and low toxicity. 11,12 Interestingly, it is reported that the g-C 3 N 4 exhibited a pH-responsive drug release which can accelerate the release of drugs in acidic environments, while releasing less drugs in alkaline and neutral environments and thus can realize targeted therapy. Unfortunately, the reported drug release ratio of g-C 3 N 4 nanosheet was only 41.4% which will lead to the waste of drug and difficulty reaching an effective concentration.…”
mentioning
confidence: 99%
“…The pseudo-first-order and pseudo-second-order models were applied to simulate the experimental kinetic data323334. Detailed information of those models is described in the Supplementary data.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption equilibrium isotherms was studied using four adsorption isothermal models including Langmuir, Freundlich, Tempkin and BET models (described in the Supplementary data) to fit the experimental data323334. The Langmuir model assumes that a monomolecular layer is formed when adsorption takes place without any interaction between the adsorbed molecules.…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, the presence of aromatic rings in the adsorbate molecule contributes highly to π−π interactions with graphenebased adsorbents. Hydrogen bonds and electrostatic interactions are the dominant heteroaggregation mechanism of GO with layered double hydroxides and oxides, such as TiO 2 , MgO, ZnO, and positively charged mineral clays (Wang et al, 2017e;Wang et al, 2016a;Zou et al, 2016b). Moreover, electrostatic interactions govern the adsorption of ionic species, such as metals and some small dyes, which frequently are used in their ionized form.…”
Section: Functionalized Graphene Its Interactions and Characterizationmentioning
confidence: 99%